Proceedings of the 42nd Annual Conference on Design Automation - DAC '05 2005
DOI: 10.1145/1065579.1065629
|View full text |Cite
|
Sign up to set email alerts
|

Minimizing peak current via opposite-phase clock tree

Abstract: Although a lot of research efforts have been made in the minimization of the total power consumption caused by the clock tree, no attention has been paid to the minimization of the peak current caused by the clock tree. In this paper, we propose an opposite-phase scheme for peak current reduction. Our basic idea is to divide the clock buffers at each level of the clock tree into two sets: an half of clock buffers operate at the same phase of the clock source, and another half of clock buffers operate at the op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…Bounded skew clock routing algorithms were developed by [27,28,29,30]. Moreover, power optimal clock buffer insertion and temperature aware clock tree optimization techniques were developed in [17] and [18], respectively, while clock buffer polarity assignment techniques were proposed for power noise reduction by [31,32,33,34]. In the 2D clock tree synthesis researches, the DME [22,23,24,25] algorithm constructs a wirelength optimal zero skew clock tree for a given tree topology under the linear delay model, and a suboptimal clock tree under the Elmore delay model [19,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Bounded skew clock routing algorithms were developed by [27,28,29,30]. Moreover, power optimal clock buffer insertion and temperature aware clock tree optimization techniques were developed in [17] and [18], respectively, while clock buffer polarity assignment techniques were proposed for power noise reduction by [31,32,33,34]. In the 2D clock tree synthesis researches, the DME [22,23,24,25] algorithm constructs a wirelength optimal zero skew clock tree for a given tree topology under the linear delay model, and a suboptimal clock tree under the Elmore delay model [19,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Rahimi [4] shows that peak current can be reduced by spreading out the clock latencies. Nieh et al [3] use an opposite-phase scheme to reduce the peak current caused by the clock tree. Wu et al [6] propose a flip-flop resynthesis technique to reduce the peak current and voltage drop by staggering the switching time of flip-flops using delay cells.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in Sapatnekar and Su [2003], it shows that 0.1V power noise will incur 79.8% inverter delay variations when the nominal V dd is 0.6V by Berkeley Predictive Technology Model with 45nm technology. 1 To reduce peak current caused by clock tree network, Nieh et al [2005] proposed an opposite-phase approach whose main idea is explained in Figures 1(a) and 1(b). In Figure 1(a), there is a binary clock tree composed of clock buffers.…”
Section: Introductionmentioning
confidence: 99%
“…Although peak current is successfully reduced in Nieh et al [2005], the power/ground noises in a local area are not. Samanta et al [2006] observed that power/ground noises are sensitive to the locations of clock buffers.…”
Section: Introductionmentioning
confidence: 99%